Rancang Bangun Game Edukasi 2D Maze Of Wisdom:Path Of Knowledge Menggunakan Godot Engine: Design and Development of the 2D Educational Game "Maze of Wisdom: Path of Knowledge" Using Godot Engine - Rizi Irama; Josua Josen A Limbong (JISTECH: Journal of Information Science and Technology, 2026)
The rapid development of information technology has encouraged the use of games as interactive learning media. However, most games mainly focus on entertainment and provide limited educational value. This study aims to design and develop a 2D  entitled Maze Of Wisdom: Path Of Knowledge using the Godot Engine. The research employed the Research and Development (R&D) method, including requirements analysis, system design using Unified Modeling Language (UML), implementation with the Godot Engine and GDScript, and functional testing using the Black Box Testing method. The developed game consists of three levels featuring maze exploration, Wisdom Scroll collection, and general knowledge quizzes to unlock the exit door. The testing results show that all main features functioned as expected. Therefore, Maze Of Wisdom: Path Of Knowledge can be used as an interactive learning medium for students and the general public through a learning-by-playing approach.